Exploratory Study on the Role of Digitalization in Improving the External Audit Quality in Public Institutions: Evidence from Morocco - Nacer Mahouat; Anas Azenzoul; Majda Chaiboub; Loubna Daoudi; Hafsa Lemsieh; Ahmed Aftiss; Khalil Mokhlis (Qubahan Academic Journal)
This study aims to understand the relationship between digitalization and the quality of external audit in public institutions, especially in the context of a developing country like Morocco. The paper adopts a qualitative approach in the form of interviews with stakeholders such as auditors, researchers and finance specialists. Data analysis was performed using NVIVO version 15 software. The results of the study show that digitalization impacts audit quality, particularly through the competence of the auditor. Indeed, this revolution pushes the practitioners of the profession to rise in theoretical and practical competency and adopt new technological tools in order to derive the best benefit from them within the scope of their mission. In addition, the relationship between digitalization and auditing can have both benefits and disadvantages mainly linked to the risk of data confidentiality and loss of human contact with the audited entity. Based on these findings, recommendations were made to ensure that the use of technology is fully aligned with the auditor’s objectives and the customer’s aspiration. The main novelty of this study is the adoption of a qualitative analysis for studying the intersection of digitalization and external audit quality in the public sector, specifically in a developing country like Morocco where the research is limited. This study is timely given the increase in the adoption of technology tools both in the public sector and in the field of audit.